IDENTIFIKASI KOMPONEN KIMIA DAN AKTIVITAS ANTIOKSIDAN DALAM TANAMAN TORBANGUN (Coleus amboinicus Lour) - Suryowati, Trini; Rimbawan, Rimbawan; Damanik, Rizal M; Bintang, Maria; Handharyani, Ekowati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe objective of this study was to determine the chemical compound in leaves, stem, and root by GC-MS technique and antioxidant activity of torbangun leaves (Coleus amboinicus Lour). The torbangun leaves ethanol extract were tested to antioxidant activity assay using DPPH, and á-glucosidase inhibitory effects was measured with a spectrophotometric method. The analysis of leaves revealed the presence of Carbamic acid, monoammonium salt (CAS) Ammonium carbamate (11.73%), Hexadecanoic acid (CAS) Palmitic acid (8.35%), I-Limonene (5.92%), Heptadecene-(8)- carbonic acid-(1) (4.76%), Oxacycloheptadec-8-en-2-one (CAS) Ambrettolide (4.70%). The analysis of stem revealed the presence of Formamide (CAS) Methanamide (22.48%), 12,13- Dimethyl-2,7- dioxa 5,10 diazatricyclo [4.4.4.0(1,6)] trans -tetradecan-12 (13.22%), Hexadecanoic acid (CAS) Palmitic acid (11.51%), 2-Propanone, 1-hydroxy- (CAS) Acetol (10.14%), 9-Octadecen-1-ol, (Z)- (CAS) cis-9-Octadecen-1-ol (7.09%). The analysis of roots revealed the presence of Methanamine, N-methyl- (CAS) Dimethylamine (28.45%), Acetic acid (CAS) Ethylic acid (9.78%), 3.2-Propanone, 1-hydroxy- (CAS) Acetol (6.41%), 1-Propen-2-ol, acetate (CAS) Isopropenyl acetate (5.16%), 4.73 Phenol, 2-methoxy- (CAS) Guaiacol(4.73%). The DPPH result of torbangun leaves ethanol extract obtained by IC50 247,942 ppm and ascorbic acid standard was 1 ppm. IC50 values inhibition of á-glucosidase extract was >100 ppm and glucobay standard was 0.264 ppm. This research provided a chemical compound and the torbangun leaves ethanol extract capable of acting as antioxidant based on IC50 values.Keywords: antioxidant activity, chemical compound, Coleus amboinicus LourABSTRAKPenelitian ini bertujuan untuk mengetahui komponen senyawa kimia dalam daun, dahan, dan akar menggunakan analisis Kromatografi Gas-Spektrometri Massa (GC-MS) serta aktivitas antioksidan daun torbangun (Coleus amboinicus Lour). Daun torbangun yang diekstrak etanol dianalisis aktivitas antioksidan menggunakan test DPPH, dan daya hambat enzim á-glukosidase diukur dengan metode spektrofotometer. Hasil analisis dalam daun menunjukkan komponen kimia Carbamic acid, monoammonium salt (CAS) Ammonium carbamate (11,73%), Hexadecanoic acid (CAS) Palmitic acid (8,35%), I-Limonene (5,92%), Heptadecene-(8)-carbonic acid-(1) (4,76%), Oxacycloheptadec-8-en-2-one (CAS) Ambrettolide (4,70%). Hasil analisis dalam dahan menunjukkan komponen kimia Formamide (CAS) Methanamide (22,8%), 12,13-Dimethyl-2,7-dioxa5,10diaza tricyclo [4.4.4.0(1,6)] trans-tetradecan-12 (13,22%), Hexadecanoic acid (CAS) Palmitic acid (11,51%), 2-Propanone,1-hydroxy-(CAS) Acetol (10,14%), 9-Octadecen-1-ol, (Z)- (CAS) cis-9-Octadecen-1-ol (7,09%). Hasil analisis dalam akar menunjukkan komponen kimia Methanamine, N-methyl-(CAS) Dimethylamine (28,45%), Acetic acid (CAS) Ethylic acid (9,78%), 3.2-Propanone, 1- hydroxy- (CAS) Acetol (6,41%), 1-Propen-2-ol, acetate (CAS) Isopropenyl acetate (5,16%), 4.73 Phenol, 2-methoxy- (CAS) Guaiacol (4,73%). Hasil uji antioksidan terhadap daun torbangun dengan metode DPPH didapatkan IC50 247,942 ppm dibandingkan standar vitamin C 1 ppm. Nilai IC50 dari penghambatan enzim á-glukosidase dalam ekstrak daun torbangun >100 ppm dibandingkan dengan standar glukobay 0,264 ppm. Hasil penelitian ini menunjukkan bahwa daun torbangun yang diekstrak dengan etanol mampu berperan sebagai antioksidan berdasarkan nilai IC50.Kata kunci: aktivitas antioksidan, Coleus amboinicus Lour, komponen kimia